Analysis of Raw Material Inventory Control Using the Economic Order Quantity (EOQ) Method: Study of Simping MSMEs, Purwakarta Regency, Indonesia - Ghiffari, M. Amirul (Arkus, 2024)
Raw material inventory is an important aspect in managing small and medium enterprises (SMEs). Effective inventory control can help SMEs increase efficiency and profitability. This research aims to analyze raw material inventory control at Simping MSMEs in Purwakarta Regency, Indonesia, using the economic order quantity (EOQ) method. Data was collected through a survey of 30 Simping MSMEs. The research results show that the EOQ method can help Simping MSMEs in determining the optimal number of raw material orders and minimizing inventory costs. Implementing the EOQ method can result in average inventory cost savings of 15% compared to the method currently used.